2019
DOI: 10.1097/adm.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Injection Drug-related Infective Endocarditis Among People Who Inject Drugs

Abstract: Objectives: Infective endocarditis (IE) among people who inject drugs is associated with high rates of mortality and repeat episodes of endocarditis. We sought to report on longer-term clinical outcomes of patients with IE who were offered buprenorphine or methadone treatment for opioid use disorder (OUD) at their initial hospital admission. Methods: Individuals with OUD hospitalized between 2013 and 2015 with IE were included for the retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Globally, the opioid epidemic has led to increasing admissions for IDU-IE, with substantial health and cost implications. 4 , 5 , 10 , 21 , 27 , 28 Our study, along with a recent study from Punjab, detected an alarming increase in the proportion of IDU-IE in India compared to the previous major IE series ( Supplementary Table 1 ). 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 A continuously increasing ratio of IDU-IE was demonstrated over the years in our study, except for a significant decline from 2014 to 2015 ( Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Globally, the opioid epidemic has led to increasing admissions for IDU-IE, with substantial health and cost implications. 4 , 5 , 10 , 21 , 27 , 28 Our study, along with a recent study from Punjab, detected an alarming increase in the proportion of IDU-IE in India compared to the previous major IE series ( Supplementary Table 1 ). 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 A continuously increasing ratio of IDU-IE was demonstrated over the years in our study, except for a significant decline from 2014 to 2015 ( Fig.…”
Section: Discussionsupporting
confidence: 57%
“…MOUD has been extensively investigated, 10 , 11 , 12 , 13 but data describing the association of MOUD receipt with mortality after IDU-IE–related hospitalization are limited. 3 , 4 , 14 , 15 A national study 9 of privately insured individuals with IDU-IE showed that MOUD was associated with decreased rehospitalizations, but smaller studies 3 , 4 , 14 , 15 investigating mortality have had conflicting results. Studies in Ontario 4 and Boston 14 found no association between MOUD receipt and long-term mortality in patients with IDU-IE; a small study in Maine 15 showed that MOUD was associated with decreased 90-day mortality only in unadjusted analyses.…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated infectious endocarditis readmission rates or repeat episodes of endocarditis and their association with MOUD ( Table 1 ) [ 28 ]. Suzuki et al [ 28 ] found that 6 (37.5%) of the 16 participants who initiated MOUD at their initial hospital admission for endocarditis had a repeat episode within the follow-up period (45 months). This did not significantly differ from those who declined MOUD during initial hospitalization and had a repeat episode (4 of 10, 40%).…”
Section: Results and Findingsmentioning
confidence: 99%
“…One study evaluated infectious endocarditis antimicrobial completion ( Table 1 ) [ 28 ]. Suzuki et al [ 28 ] noted that there was no significant difference in completion of antimicrobial course for endocarditis in those on MOUD compared with those not on MOUD.…”
Section: Results and Findingsmentioning
confidence: 99%
See 1 more Smart Citation